PEMBELAJARAN VOKAL UNTUK MENCAPAI KETEPATAN NADA DALAM MEMBACA PARTITUR PADUAN SUARA PADA EKSTRAKULIKULER VOKAL SMPN 8 DENPASAR - Ririmasse, Yorico Christy; Darmayuda, I Komang; Laksmi, Desak Made Suarti (MELODIOUS : JOURNAL OF MUSIC, 2024)
This research, entitled "Vocal Learning to Achieve Tone Accuracy in Reading Choral Scores at Vocal Extracurricular at SMPN 8 Denpasar", is motivated by students' lack of understanding in singing each note properly and correctly. In a choir, the accuracy of a singer's tone is absolutely essential so that the song sung sounds good. The aim of this research is to increase sensitivity to tone through various vocal techniques provided by the author. There is one vocal technique that according to the author needs to be studied in order to achieve pitch accuracy, namely the intonation technique. Apart from that, it is not enough to just learn vocal techniques, but it is also necessary to learn basic music theory in reading choral scores. The music theory in question is reading the number notation or solmization properly and correctly, knowing the value of the number notes and also understanding the chart of the song being sung. The learning methods used in this research are the lecture method, discussion method, question and answer method, and demonstration method. Data collection was obtained through interviews, document studies, and direct observation of the learning process that occurred. The extracurricular vocal class students at SMPN 8 Denpasar became the research objects. The expected achievement target is to achieve the learning objectives that have been set.